Contesting perception: The genesis of Islamic architecture idioms in the Sultanates Mosques of British Malaya 1874-1957 - Md Sharif, Harlina (Masjid Al-Azhar, Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2016)
The advent of the 20th century witnessed the emergence of congregation mosques (masjid al’jami’), built in Neo-classical, Avant-Garde and Mughal repertoires, replacing traditional-vernacular styles. Mosques especially attributed to the Malay Sultans, were particularly outstanding for their scale, materials and design. Many of them were fully or partially funded by the British rule, or presented to the Malay ruler as a gift. The study looks at the transformations of the mosque idioms as seen in sultanate mosques built during the British Rule. By carrying out visual survey on these mosques, the study highlights factors causing the morphology of a mosque’s physical language and characteristics, and argues that the genesis of the “Islamic Architecture” idioms in Malaysia was actually founded during the British administration in pre-independence Malaysia.